Tailoring manganese dioxide electrocatalyst by platinum and carbon nanotube for air-cathode microbial fuel cell - Woon, Chee Wai (2017)
Air cathode microbial fuel cell (MFC) is a high potential green technology which could simultaneously generate bio-electricity and conducting wastewater treatment. However, the slow oxygen reduction reaction (ORR) is one of the limiting factors that bounds the power generation of the cell. Hence, ORR catalytic electrocatalysts are required to enhance the performance of the air-cathode MFC. Platinum (Pt) is the conventional electrocatalysts which have been used for various applications as it has the preeminent ORR catalytic activity with high stability. However, the precious metal electrocatalyst creates a big obstacle in the development and application of Pt electrocatalysts in MFCs. Therefore, alternative ORR electrocatalysts were developed to replace the Pt electrocatalyst. In recent years, manganese dioxide (MnO2) has been studied extensively and found that it has a great potential as an effective ORR electrocatalyst due to its unique properties, low cost, easy preparation and possesses ORR catalytic activity. However, the ORR activity of MnO2 is still low compared to that Pt electrocatalyst due to the intrinsic low electrical conductivity of MnO2. Therefore, modifications are needed to enhance the ORR activity of MnO2 to substitute the Pt electrocatalyst in air-cathode MFC application. In present work, MnO2 was developed via hydrothermal method and modified by incorporating trace amount of Pt nanoparticles, carbon nanotube (CNT) and both Pt and CNT to develop Pt/MnO2, MnO2/CNT and Pt-MnO2/CNT, respectively. The goal of this work is to develop an effective ORR electrocatalyst for improving the performance of the MFC for power generation and simultaneously treating palm oil mill effluent (POME). The as-prepared electrocatalysts were characterized comprehensively through Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray analysis (EDX), Fourier Transform Infrared Spectroscopy (FT-IR), X-ray Diffraction analysis (XRD), X-ray Photoelectron Spectroscopy (XPS), Brunauer-Emmett-Teller analysis (BET), Cyclic Voltammetry (CV), Linear Sweep Voltammetry (LSV), Electrochemical Impedance Spectroscopy (EIS) and Mott-Schottky analysis where the surface morphology, crystallinity, oxidation state and electrochemical activity of the as-prepared electrocatalysts were examined, respectively. The effectiveness of the electrocatalysts were tested in the air-cathode MFC with POME and anaerobic sludge as the anolyte and inoculum, respectively. The performance of the MFC was determined via polarization test. The stability, coulombic efficiency (CE) and chemical oxygen demand (COD) removal efficiency of the MFC with the respectively electrocatalysts were investigated. As the result, Pt-MnO2/CNT was found to be the best ORR electrocatalysts among the modified electrocatalysts which has the highest ORR activity with lowest total and charge transfer resistances which showed high stability and the highest maximum power density, open circuit potential (OCP), CE and COD removal efficiency of 100.63 mW/m2, 629.30 mV, 34.17% and 75.55%, respectively. From the study, it was found that the presence of the CNT increases the BET surface area and the conductivity of the electrocatalyst meanwhile the presence of Pt increases the ORR catalytic activity, conductivity and the stability of the electrocatalysts. By the combination of both Pt and CNT in the MnO2 electrocatalyst, a high ORR catalytic activity with high conductivity, stability and BET surface area electrocatalyst (Pt-MnO2/CNT) was developed which showed an improved MFC performance, operational stability and COD removal efficiency.